1996
DOI: 10.1524/ract.1996.72.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium Isotopie Composition in Soil from the Former Semipalatinsk Nuclear Test Site

Abstract: This paper reports preliminary results on plutonium isotopie composition in soil sampled at the Semipalatinsk Nuclear Test Site in the former USSR. The soil was sampled in October 1994 from two locations in the test site, the first nuclear explosion site and the bank of the crater called "Bolapan" along the Shagan River Site. The Pu isotopie composition of these samples was determined through the measurements of ""Pu/^Pu (and 242 Pu/ 239 Pu) atom ratios by high resolution ICP-MS, 24 'Pu by a low background liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…As seen in the last column of Table 2, all soil samples measured have very low 240 Pu/ 239 Pu atomic ratios of 0.025 -0.072. These values are close to 0.036 found previously for the surface soil sample from ground zero [6], and are significantly lower than 0.18 commonly found for global fallout Pu. Using the equation described by Hardy et al [12], the combined Pu radioactivity in the samples shown in Table 2 can be resolved to give Semipalatinsk fraction from the 240 Pu/ 239 Pu atomic ratios.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…As seen in the last column of Table 2, all soil samples measured have very low 240 Pu/ 239 Pu atomic ratios of 0.025 -0.072. These values are close to 0.036 found previously for the surface soil sample from ground zero [6], and are significantly lower than 0.18 commonly found for global fallout Pu. Using the equation described by Hardy et al [12], the combined Pu radioactivity in the samples shown in Table 2 can be resolved to give Semipalatinsk fraction from the 240 Pu/ 239 Pu atomic ratios.…”
Section: Resultssupporting
confidence: 82%
“…On the other hand, for the measurement of the 240 Pu/ 239 Pu atomic ratio, an aliquot of 10-30 g of the soil sample was treated in a manner similar to the method described above, in the absence of a yield tracer such as 242 Pu. Plutonium in each fraction obtained from the above procedures was separated and purified by using radioanalytical method described in detail by Yamamoto et al [5], and activities of 238 Pu and 239 -240 Pu were determined by «-spectrometry following electrodeposition [5], The 240 Pu/ 239 Pu atomic ratio was determined by high resolution inductively coupled plasma mass spectrometry [6].…”
Section: Radioactivity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were purified with extraction chromatography, using UTEVA Ò and TRU Ò resins (Eichrom Technologies) to lower the concentrations of the interfering radionuclides (especially U) before determining the Pu isotopes with ICP-MS (Fig 1). After the Table 1 Mass ratios 240 Pu/ 239 Pu, 238 Pu/ 239 Pu, and 241 Pu/ 239 Pu from different sources in Northern Hemisphere relevant to samples of this study (Hardy et al, 1973;Holm et al, 1992;Irlweck and Hrnecek, 1999;Kashparov et al, 2003;Kelley et al, 1999;Krey et al, 1990;Muramatsu et al, 2000Muramatsu et al, , 2001UNSCEAR, 2000;Warneke et al, 2002;Yamamoto et al, 1996). Hrnecek et al (2008), Lee et al (2001), and Muramatsu et al (1999Muramatsu et al ( , 2001, for the IAEA-135 reference sediment.…”
Section: Purification Of Old Alpha Samplesmentioning
confidence: 95%
“…3-6 Previously, we reported the current radioactive contamination levels of the land from 137Cs and Pu isotopes within the territory of the test site. [7][8][9] We collected further soil samples on residual radioactivity measurements and brick samples on thermoluminescence dosimetry measurements at the areas outside the territory of the test site, including some settlements of Mostik, Dolon, Chagan and so on, where * E-mail: pluto@kenroku.kanazawa-u.ac.jp…”
Section: Introductionmentioning
confidence: 99%